Understanding the spark plasma sintering from the view of materials joining. (October 2016) - Dong, Peng; Wang, Zhe; Wang, Wenxian; Chen, Shaoping; Zhou, Jun
Abstract: Spark plasma sintering (SPS) is an attractive consolidation process. However, the mechanism behind this process is still an open topic for debate. This paper presents the first attempt to understand the SPS mechanism from perspective of materials joining. For this, TiNif /Al composites were fabricated by SPS, and the interfacial microstructures were investigated using field emission scanning electron microscopy and transmission electron microscopy. According to the experimental results, several joining processes were reflected well during SPS, involving micro-arc welding, electric resistance welding and diffusion welding. The proposed understanding of SPS will be helpful to the control of sintering quality. Graphical abstract: